Trichomonas vaginalis and prostate cancer: A systematic review (Research, Society and Development, 2024)
Introduction: Prostate cancer (PC) is the second most frequent neoplasm in men accounting for 29% of tumor cases, at a rate of 1.4 million new cases and 375,000 deaths globally each year. Although its high prevalence, little is known about its etiology. Sexually transmitted infections (STIs) are one of the factors under discussion for a possible risk factor. Trichomoniasis is a prevalent STI caused by the pathogenic protozoan Trichomonas vaginalis that has been associated with the incidence of PC. Objectives: This review aims to determine whether the T. vaginalis is a risk factor for the development and/or progression of the disease. Methodology: A systematic review was conducted using the PubMed and Scielo databases. The following descriptors were used: “Prostate Cancer”; “Trichomonas vaginalis”; “Trichomonosis”; “Prostate”, all indexed in DeCS/MeSH. Results and Discussion: In total, 24 articles were included (8 in vitro studies; 1 in vivo study; 3 prospective studies; 9 case-control studies; 2 randomized clinical trials; and 1 systematic review and meta-analysis). Conclusion: Even though in vitro and in vivo studies analyzed credibly indicate the existence of this pathophysiology, these findings have not been reproduced in most populations studies conducted, throughout the years. More recent studies involving a bigger database indicates an association. This leads us to believe that new population studies should be conducted to obtain a consensus so that educational and preventive measures can be implemented.